Evaluation of Green Area Criteria Assessment in Indonesia: A Systematic Literature Review - Abubakar, Muhammad Rizky; Fitriaty, Puteri; Arief, Irdinal (KBK Peracangan Arsitektur dan Kota Program Studi Arsitektur Fakultas Pendidikan Teknologi, 2025)
This study aims to evaluate the application of green area assessment tools in Indonesia through a systematic literature review. The method employed includes a literature search from 2016 to 2024 using Publish or Perish with databases from Google Scholar, Crossref, and Semantic Scholar, as well as the application of the PRISMA methodology for article selection. This study also involves bibliometric analysis using VOSviewer to map the relationships between keywords. The results show that the application of the green area concept is more focused on the operational phase, with 50% of research concentrated in this area. The Greenship Neighborhood v.1.0 assessment tool is the most dominant, while BGH PUPR is still rarely used. Cluster analysis identifies four main categories in the research, including implementation, location, indicators, and assessment tools. The findings indicate a lack of research in underrepresented sectors such as transportation and industrial facilities, as well as the need for more comprehensive exploration throughout the entire life cycle of buildings. This study recommends the development of policies to support the wider adoption of green area assessment tools and further training for developers. It is expected that the results of this study will contribute to enhancing the implementation of green area concepts in Indonesia, supporting environmental sustainability and more eco-friendly development.